Answer:
j = (G - 4)/3
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
- Multiplication Property of Equality
- Division Property of Equality
- Addition Property of Equality
- Subtraction Property of Equality
Explanation:
Step 1: Define
G = 3j + 4
Step 2: Solve for j
- [Subtraction Property of Equality] Subtract 4 on both sides: G - 4 = 3j
- [Division Property of Equality] Divide 3 on both sides: (G - 4)/3 = j
- Rearrange/Rewrite: j = (G - 4)/3